Effectiveness and Safety of Apixaban, Low-Molecular-Weight Heparin, and Warfarin among Venous Thromboembolism Patients with Active Cancer: A U.S. Claims Data Analysis - Cohen, Alexander; Keshishian, Allison; Lee, Theodore; Wygant, Gail; Rosenblatt, Lisa; Hlavacek, Patrick; Mardekian, Jack; Wiederkehr, Daniel; Sah, Janvi; Luo, Xuemei (Thrombosis and Haemostasis, 2020)
Background This study primarily evaluates the risk of recurrent venous thromboembolism (VTE) and major bleeding (MB) among patients with VTE and active cancer prescribed apixaban, low-molecular-weight heparin (LMWH), or warfarin, with claims data.Methods Four U.S. commercial insurance claims databases were used to identify patients with VTE and active cancer who initiated apixaban, LMWH, or warfarin within 30 days following the first VTE event. Stabilized inverse-probability treatment weighting (IPTW) was used to balance treatment cohorts. Cox proportional hazard models were used to evaluate risk of recurrent VTE and MB.Results All eligibility criteria were fulfilled by 3,393 apixaban, 6,108 LMWH, and 4,585 warfarin patients. After IPTW, all patient characteristics were balanced. When the follow-up was censored at 6 months, apixaban patients had a lower risk of recurrent VTE (hazard ratio [HR]: 0.61; 95% confidence interval [CI]: 0.47–0.81) and MB (HR: 0.63; 95% CI: 0.47–0.86) versus LMWH. Apixaban patients had a lower risk of recurrent VTE (HR: 0.68; 95% CI: 0.52–0.90) and similar risk of MB (HR: 0.73; 95% CI: 0.53–1.00) versus warfarin. Warfarin patients had a similar risk of recurrent VTE (HR: 0.91; 95% CI: 0.72–1.15) and MB (HR: 0.87; 95% CI: 0.68–1.12) versus LMWH. The trends were similar for the entire follow-up; however, apixaban patients had a lower risk of MB versus warfarin patients.Conclusion Patients with VTE and active cancer who initiated apixaban had a lower risk of recurrent VTE and MB compared with LMWH patients. Apixaban patients also had a lower risk of recurrent VTE compared with warfarin patients.
Keywords: venous thromboembolism; anticoagulant; major bleeding; recurrent VTE; cancer-associated VTE